An Alloantibody Recognizing the FVIII A1 Domain in a Patient with CRM Reduced Haemophilia A due to Deletion of a Large Portion of the A1 Domain DNA Sequence - Shibata, Masaru; Shima, Midori; Morichika, Shogo; McVey, John; Tuddenham, Edward G. D.; Tanaka, Ichiro; Suzuki, Hiroshi; Nogami, Keiji; Minamoto, Yohko; Hato, Takaaki; Saenko, Evgueni L.; Scandella, Dorothea; Yoshioka, Akira (Thrombosis and Haemostasis, 2000)
We report the development of a FVIII inhibitor in a patient with severe, cross reacting material reduced (CRMR) haemophilia A. The level of Factor VIII antigen (FVIII:Ag) measured by ELISA using anti- C2 monoclonal and alloantibodies was 1.9 U/dl. This baseline FVIII:Ag level was increased to 8.3 U/dl after administration of DDAVP. The anti-FVIII inhibitor titer was 2.9 Bethesda U/ml. DNA analysis showed a large deletion of the FVIII gene from exon 4 to 7, corresponding to amino acid residues 111-317 included within the A1 domain. The size of the gene deletion was approximately 28 kb. 5' and 3' breakpoints were identified by sequencing in intron 3 and intron 7, respectively. FVIII mRNA was detected in the patient’s peripheral lymphocytes and the deletion spanning exon 4 to 7 was confirmed at the RNA level. Immunoprecipitation experiments using 125I labeled A1, A2 and light chain demonstrated that the inhibitor reacted only with the 54 kDa A1 domain. The inhibitor activity was more than 95% neutralized by A1 domain polypeptide. Our findings suggest a close relationship between the inhibitor epitope and the specific gene deletion with regard to the pathogenesis of the inhibitor in this patient.
Keywords: Haemophilia A; inhibitor; A1 domain; gene deletion; factor VIII; cross-reacting material reduced